Estudo da produção de biodiesel etílico de chichá (Sterculia striata) e do equilíbrio de fases líquido-líquido para o sistema contendo biodiesel + álcool + glicerina - Gomes Filho, João Correia (2013)
Although the interest in vegetable oils as feedstock for biofuel production is not a recent issue, this took great impetus by the need to have alternative energy sources to the use of oil and oil products, with a search for new sources of vegetable oil. The chichá (sterculia striata) is a large tree that measures 8-25 meters high, it is found in the Brazilian Atlantic Forest and it has fast growing, resistance to low temperatures and different altitudes. The seeds are cylindrical and flat with a black fur that comes off as dries. It has up to 42%almond oil, being a potential candidate for obtaining oil in Brazil. In recent years, many researches have been developed in order to make the production of biodiesel, by ethylic route, technically and economically viable. In this point, much has been done with respect to reactional aspects of this process. However, little researches have been done in order to solve problems related to separation and purification steps. Knowing the phase behavior of the systems is vital for the design, operation and control of these units. This study aimed to: 1) study the process of obtaining biodiesel from chichá oil, 2) perform experimental and theoretical study of the liquid-liquid equilibrium (LLE) involving representative substances of the phase equilibrium present in the chichá biodiesel production. It is expected that the experimental results obtained in this study may come to assist the industry of biodiesel production, providing biodiesel production data and phase equilibrium data to these ones. The results showed that the chichá has about 40% oil in its seed, the chichá biodiesel production reached 99% yield in esters using time ration of 0,5 hours, molar ratio oil/alcohol 1/10, 1,5 % oil mass in mass of catalyst and temperature of 30 °C. The data (LLE) for the ternary system chichá biodiesel + ethanol + glycerol and its tie-lines showed a very characteristic behavior, having no significant variation in studied temperatures.